KAJIAN HUKUM PENGGUNAAN PUKAT HARIMAU DALAM PENANGKAPAN IKAN: Judical Review Of The Use Of Trawl In Fishing - Adam Rizky Hidayat; Dyah Setyorini (Reformasi Hukum Trisakti, 2024)
This research discusses the impact of the use of illegal fishing gear, especially trawlers, on the welfare of small fishermen in Tanggamus Regency, Lampung Province. Through interviews with Head Fishermen and partners from Polair, this research identified that despite the ban on the use of trawls based on Law Number 45 of 2009 concerning fisheries, some small fishermen are still reluctant to switch to legal fishing gear. The formulation of the problem is what is the legal regulation of the use of trawls in fishing and how is the use of trawls in fishing by fishermen in the Tanggamus Regency area, Lampung Province in terms of Law Number 45 of 2009 concerning Amendments to Law Number 31 of 2004 concerning Fisheries? The Normative Juridical research method is descriptive analytical, then analyzed qualitatively, then conclusions are drawn using a deductive mindset. The results:several alternative fishing gear such as gill nets, hand lines, basic longline fishing, drift longline fishing, payang fishing gear, and payang nets. The social and cultural implications in small-scale fishers' decisions are also a focus for understanding the challenges faced in changing their traditional practices. Conclusion: provides an overview of the complexity of changes in behavior of small-scale fishermen.